PROPOSED SOCIO-ENVIRONMENTAL DESIGN FACTORS (SEDeF) MODEL AS RESIDENTIAL NEIGHBOURHOOD CRIME PREVENTION STRATEGY IN NIGERIA. - Olajide, Sunday Emmanuel (Advances in Social Sciences Research Journal, 2017)
Housing is considered essential human need as it is ranked next to food for obvious reasons like provision of living accommodation, investment opportunities, social and recreation services among others. However, its relevance to humanity is gradually being eroded as a result of the threat from residential neighbourhood crime in the form of burglary and theft, vandalism, incivilities and street crime, robbery and even violent crime. In Nigeria, it was found that the use of penal system (use of police, prison and courts) for crime control is prevalent which researchers have described to be grossly inadequate. Hence, the intention of this research is to empirically analyse the desirability of the proposed socio-environmental design factors (SEDeF) model as a more effective technique to curb residential neighbourhood crime in Nigeria. One Thousand (1000) sets of structured questionnaire were administered on the residents of residential estates within the South Western States of Nigeria out of which 467 were considered useable after the data screening. Purposive and systematic sampling techniques were adopted while logistic regression was used to determine the impact of the various components of each factor. The results showed a significant probability of 0.0007 and 0.0025 for environmental design factors and social development factors respectively establishing the desirability of the model in residential neighbourhood crime prevention. The policy implication of this result is that if government can intensify effort in the use of social development factors (SDF) and environmental design factors (EDF), the soaring trend of residential neighbourhood crime would be curtailed. Key words: Crime prevention; Logistic regression; Nigeria; Residential neighbourhood crime; SEDeF.